Factors of Ethical Decline and Religious Measures to Overcome - Sultana, Munazza; Bukhari, Syed Abdul Ghaffar (Journal of Islamic and Religious Studies, 2020)
This article aims to investigate the causes and factors involved in the moral decline of youth and its solution in the light of Islamic teachings. It is generally observed that the students studying at various education levels, especially undergraduate students of universities are seriously lacking in moral values and their ethical conduct is not satisfactory. Research shows that factors of bad conduct include, less emphasis on the moral conduct of students at secondary and higher secondary levels, lack of parent’s interest in building their children's attitude and least efforts by the religious scholars and government institutions in morale building. To preserve a nation on its Culture and Values, character building is one of its important aspects, based on religious norms and principles. Positive building constructs approach to promote behavioral, social, emotional, and moral competence and raises spirituality, self-efficiency, loyalty, confidence, identity, and prosaically norms. The findings of this research highlight that there is a correlation between the ethical conduct of students and their university environment, which brings changes in human personality and character development. Social illnesses and moral deterioration are rooted in the behavior of the students, which they usually acquire from the home and university environment.